(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is emphasized that Bahauddin Naqshband called all people in the society to be a friendly alliance with each other and not to fight against bad people through words, not to hate them, but to realize that he is also a human being, understand his mistakes and help him to take a place among good people.